Effectiveness of cognitive–behavioural therapy: a protocol for an overview of systematic reviews and meta-analyses. Issue 12 (14th December 2018) - Fordham, Beth; Sugavanam, Thavapriya; Hopewell, Sally; Hemming, Karla; Howick, Jeremy; Kirtley, Shona; das Nair, Roshan; Hamer-Hunt, Julia; Lamb, Sarah E
Abstract : Introduction: Cognitive–behavioural therapy (CBT) is a psychological therapy that has been used to improve patient well-being across multiple mental and physical health problems. Its effectiveness has been examined in thousands of randomised control trials that have been synthesised into hundreds of systematic reviews. The aim of this overview is to map, synthesise and assess the reliability of evidence generated from these systematic reviews of the effectiveness of CBT across all health conditions, patient groups and settings. Methods and analysis: We will run our search strategy, to identify systematic reviews of CBT, within the Database of Abstracts of Reviews of Effects, the Cochrane Library of Systematic Reviews, MEDLINE, Embase, PsycInfo, CINAHL, Child Development and Adolescent Studies, and OpenGrey between January 1992 and 25 April 2018. Independent reviewers will sift, perform data extraction in duplicate and assess the quality of the reviews using the Assessing the Methodological Quality of Systematic Reviews (V.2) tool. The outcomes of interest include: health-related quality of life, depression, anxiety, psychosis and physical/physiological outcomes prioritised in the individual reviews. The evidence will be mapped and synthesised where appropriate by health problem, patient subgroups, intervention type, context and outcome. Ethics and dissemination: Ethical approval is not required as this is an overview of published systematic reviews. We plan to publish results in peer-reviewed journals and present at international and national academic, clinical and patient conferences. Trial registration number: CRD42017078690.